Impact of pre-pregnancy excessive body weight on the composition of polyunsaturated fatty acids in breast milk: a systematic review. (17th February 2020) - Amaral, Yasmin; Marano, Daniele; Oliveira, Elissa; Moreira, Maria Elisabeth
Abstract: This study aims to identify through a systematic review the possible effects of pre-gestational excessive body weight on the composition of polyunsaturated fatty acids in human milk. The papers were selected in the following databases: PubMed, Virtual Health Library, EMBASE, Web of Science and SCOPUS. The search strategy employed descriptors: 'Human Milk' AND 'Obesity' OR 'Overweight' OR 'Body Mass Index' AND 'Fatty acid' OR 'Omega3' OR 'Omega6'. According to the established strategy, six manuscripts were selected. Most of the selected studies concluded that mothers with excessive body weight presented a milk with a higher concentration of omega 6. In addition, all selected studies identified an increased Omega-6/Omega-3 ratio in the milk of pre-gestational excessive body weight mothers compared to the eutrophic ones. The milk of pre-gestational excessive body weight women had a higher Omega-6/Omega-3 ratio, which confirms the importance of starting pregnancy with adequate weight, thus minimising the possible influences that excessive body weight can cause infant health.